Postural therapy for renal stones in children: A Rolling Stones procedure. Issue 4 (August 2016) - Faure, A.; Dicrocco, E.; Hery, G.; Boissier, R.; Bienvenu, L.; Thirakul, S.; Maffei, P.; Panait, N.; Karsenty, G.; Merrot, T.; Alessandrini, P.; Guys, J.-M.; et al.
Summary: Introduction: Despite many advances, the management of renal stones – especially lower caliceal stones (LCS) – remains a challenge. The gravity-dependent location of the lower calices hinders the spontaneous clearance of fragments, which can be a nidus for future growth and symptomatic recurrence. Currently, there is no standard adjunctive therapy to facilitate fragment passage. Objectives: To report the safety and effectiveness of mechanical percussion diuresis and inversion (PDI) therapy for eliminating renal stones in children. Patients and Methods: Since November 2013, children with residual fragments (after shock wave lithotripsy or flexible ureteroscopy) or native symptomatic renal stones were prospectively included in a protocol of four PDI sessions. After giving written consent, the children drank 10 ml/kg of water 30 min before therapy. They then laid in a prone Trendelenburg position on a couch angled at 45° and received continuous 10-min mechanical percussion applied over the affected flank by a physiotherapist (Figure summary). Tolerance stone burden reduction and stone clearance were documented with ultrasound 4 weeks after the last session. Results: Seventeen participants, with a median age of 10.8 years (range 18 months to 18 years), received 82 PDI sessions performed over 22 months. The median stone diameter was 5 mm (range 3–9). All children tolerated the PDI therapy well. Over a median follow-up of 11 months (range 3–18), no significant adverse effects were noted. The overall stone-free rate was 65%. Four of the six patients with residual fragment passed their fragments. The patients who did not become stone free by PDI experienced a decrease in fragment size of 57% (range 34–71). The observance rate was 100%. Discussion: Many studies have demonstrated that the gravity-dependent position of the lower calyces appears to be an important factor limiting the clearance of LCS. Positioning patients with a degree of inversion in order to put the collecting system beyond the horizontal plane affected the LCS through gravitational force. Complications were rare. PDI appeared to save costs and have similar success rates as shock wave lithotripsy for native small renal stones in children. Conclusion: PDI is safe and effective for facilitating gravity-dependent drainage of renal stones and provides an opportunity to treat children in a quick, non-invasive, economic, painless, non-radiative and diverting fashion. This therapy is a valuable alternative in the pattern of stone management. In case of persistent fragments, it is recommend that the number of sessions be increased to six. Figure Adolescent girl receiving mechanical percussion and inversion treatment.